2002
DOI: 10.1590/s0104-11692002000600002
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida do idoso na comunidade: aplicação da Escala de Flanagan

Abstract: Esse estudo objetivou avaliar a satisfação de idosos em relação à sua qualidade de vida. Os dados foram obtidos através de questionário que caracterizava a amostra e a Escala de Qualidade de Vida de Flanagan, utilizando-se a técnica de entrevista. A amostra foi constituída por 128 idosos. Nos resultados, verificamos que a satisfação desses idosos mostrou-se regular. As dimensões da qualidade de vida apontadas na escala de Flanagan foram: desenvolvimento pessoal e realização; relações com familiares; participaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
61

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 3 publications
2
28
0
61
Order By: Relevance
“…In contrast, another study reported full satisfaction with activities performed in community groups, which are involved in social and religious actions that act as facilitators for interaction and development of new friendships, expanding the circle of social support. 23 While the score for the domain death and dying was the highest (68.4) among our respondents, most reported being too afraid of feeling any pain in the process of death, which was also observed in other studies that used the WHOQOL-OLD. [33][34][35] Despite the many effective drugs for pain relief, these patients are often inadequately treated, especially when the caregiver has limited access to information or is afraid to medicate, which would explain the results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, another study reported full satisfaction with activities performed in community groups, which are involved in social and religious actions that act as facilitators for interaction and development of new friendships, expanding the circle of social support. 23 While the score for the domain death and dying was the highest (68.4) among our respondents, most reported being too afraid of feeling any pain in the process of death, which was also observed in other studies that used the WHOQOL-OLD. [33][34][35] Despite the many effective drugs for pain relief, these patients are often inadequately treated, especially when the caregiver has limited access to information or is afraid to medicate, which would explain the results.…”
Section: Discussionsupporting
confidence: 82%
“…There were difficulties previously described in the literature for the application of the WHOQOL-BREF, WHOQOL-OLD and SF-36 questionnaires to the frail elderly population. These were related to the very application of the questionnaires [23][24][25] and the studied population. Cognitive and physical conditions of the elderly limited participation in the research.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, social status directly impacts living conditions and health status in the elderly. Income is one of the main concerns for the elderly according to another study in this population 49 , thus highlighting this variable's importance in experiencing old age with quality.…”
Section: Discussionmentioning
confidence: 77%
“…Some studies have shown that lower-income elderly are more susceptible to disease, disability, and dependency 49 . According to Coelho Filho & Ramos 48 , elders living in poorer areas of Fortaleza, Ceará State, Brazil, showed greater physical and mental morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…It is de ined by the individual as an internal experience of satisfaction and well-being in their living process (11,12).…”
Section: Introductionmentioning
confidence: 99%